Oxygen carriers for the chemical looping combustion of MSW syngas and HCl removal - Boon, Yinn Zhao (Nanyang Technological University, 2020)
The simultaneous removal of HCl during the Chemical Looping Combustion (CLC) process of syngas produced from municipal solid waste (MSW) gasification was investigated using the iron ore (IO) doped with HCl sorbents as the oxygen carriers (OCs). Two different HCl sorbents, i.e. witherite and limestone, were physically mixed with IO for comparison on their ability in removing HCl. The effects of these sorbents on the CLC performance of IO were also investigated. A bench-scale fluidized bed reactor was used to conduct the performance tests. Some variations in the operation conditions for the tests were made, including temperature, HCl concentration in the input reduction gas stream, and the loading ratio of sorbents. To investigate the reactivity of the OCs, thermogravimetric analysis (TGA) was carried out for IO before and after sorbents loading. It was found that the doping of witherite significantly improved both the reaction rate and the oxygen transport capacity of IO due to the increased oxygen vacancies. The presence of HCl in the syngas showed minor effect on CO combustion efficiency, while a positive effect on H2 combustion efficiency was observed. The pristine IO can scarcely remove HCl in the syngas due to the thermodynamically unfavorable for the reaction between Fe2O3 and HCl. By contrast, loading with 10 wt% witherite increased the HCl removal efficiency to above 90% for 10 consecutive cycles with 500ppmV HCl input at 850℃, and this is much higher than the HCl absorption ability demonstrated by 10 wt% limestone-doped IO. The findings show that the witherite-doped IO could be a promising OC for the CLC process of syngas that contains HCl.